Risk factors of hepatitis B virus infection in children. - Rukunuzzaman, M; Afroza, A (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):700-8 The abstract of this article is available on the PubMed website